Effect of Solidification Rate and Rare Earth Metal Addition on the Microstructural Characteristics and Porosity Formation in A356 Alloy - M. G. Mahmoud; A. M. Samuel; H. W. Doty; S. Valtierra; F. H. Samuel (Advances in Materials Science and Engineering)
The present study was performed on A356 alloy with the main aim of investigating the effects of La and Ce additions to 356 alloys (with and without 100 ppm Sr) on the microstructure and porosity formation in these alloys. Measured amounts of La, Ce, and Sr were added to the molten alloy. The results showed that, in the absence of Sr, addition of La and Ce leads to an increase in the nucleation temperature of the α-Al dendritic network with a decrease in the temperature of the eutectic Si precipitation, resulting in increasing the freezing range. Addition of 100 ppm Sr results in neutralizing these effects. The presence of La or Ce in the casting has a minor effect on eutectic Si modification, in spite of the observed depression in the eutectic temperature. It should be noted that Ce is more effective than La as an alternate modifying agent. According to the atomic radius ratio, rLa/rSi is 1.604 and rCe/rSi is 1.559, theoretically, which shows that Ce is relatively more effective than La. The present findings confirm that Sr is the most dominating modification agent. Interaction between rare earth (RE) metals and Sr would reduce the effectiveness of Sr. Although modification with Sr causes the formation of shrinkage porosity, it also reacts with RE-rich intermetallics, resulting in their fragmentation.